2012
DOI: 10.2478/v10011-011-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transitory Hyperprolactinemia on Clinical Outcome of In Vitro Fertilization and Embryo Transfer

Abstract: Summary: This study aimed to evaluate the impact of serum prolactin concentration at the day of human chorio nic gonadotropin (HCG) administration on the clinical outcome of in vitro fertilization and embryo transfer (IVF-ET). A total of 184 patients receiving the IVF-ET/ICSI-ET from Octo ber 2005 to March 2008 were retrospectively analyzed. Sub jects were divided into four groups according to the serum prolactin concentration [<30 ng/mL (A), 30-60 ng/mL (B), 60-90 ng/mL (C), ≥90 ng/mL (D)] on the day of HCG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…This seems to be the case in the current study, as LH was not elevated, and similar LH concentrations were observed in both groups. P elevation varies widely among reports (e.g., 0.8 ng/ml and 9.54 nmol/l) [ 8 , 27 ]. In our study, a P level ≥1.3 ng/ml was set as the threshold to define PPE, and the incidence of PPE was found to be 32.6%, which is consistent with the 38.3% reported by Bosch et al and 36.7% reported by Li et al [ 8 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be the case in the current study, as LH was not elevated, and similar LH concentrations were observed in both groups. P elevation varies widely among reports (e.g., 0.8 ng/ml and 9.54 nmol/l) [ 8 , 27 ]. In our study, a P level ≥1.3 ng/ml was set as the threshold to define PPE, and the incidence of PPE was found to be 32.6%, which is consistent with the 38.3% reported by Bosch et al and 36.7% reported by Li et al [ 8 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence supports the pleiotropic role of prolactin in reproduction, growth, metabolism, electrolyte transport, behaviour, immunity and carcinogenesis [ 1 ]. Regarding the physiological effects, aside from the traditional role on lactation, several studies have suggested a more complex role of prolactin in reproduction by its benefic effects on oocytes development [ 2 , 3 , 4 , 5 ], corpus luteum formation and survival [ 6 ], implantation [ 7 ], steroidogenesis [ 8 , 9 ] and immunomodulatory effects [ 10 , 11 ]. Thus, a certain level of circulating prolactin might be necessary for optimal reproductive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…During the menstrual cycle, fluctuations of the prolactin level were noticed, supporting the involvement of prolactin in variate aspects of reproduction. During controlled ovarian stimulation (COS) for assisted reproductive technology a particular dynamic of serum prolactin level, characterized by transient hyperprolactinemia, was also reported [ 8 , 12 , 13 ] with incompletely known significance and impact on fertility treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…It may also interfere with the function of the corpus luteum resulting in luteal phase defects as well as irregular implantation and embryo growth. Speci ic studies have shown the presence of a state of Hyperprolactinemia during cycles of IVF / Intracytoplasmic Sperm Injection (ICSI) (Zhong et al, 2012;Boyers et al, 1987). In the early stages of pregnancy, hCG is luteotropic, preserving progesterone development and endometrial support.…”
Section: Introductionmentioning
confidence: 99%